2022
DOI: 10.3389/fcimb.2021.823403
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Utilizes lncRNAs to Activate the Anti-Dengue Toll Pathway and Balance Reactive Oxygen Species Stress in Aedes aegypti Through a Competitive Endogenous RNA Network

Abstract: Long non-coding RNAs (lncRNA), a class of RNA molecules without protein coding potential, are more than 200 nucleotides in length and widely present in a variety of species. Although increasing progress in regard to the determination of lncRNA function has been made in vertebrates, Aedes aegypti lncRNAs were only identified recently and the functions of few lncRNAs have been annotated so far. Herein, the genome-wide alteration of the lncRNA expression profile trigged by Wolbachia wAlbB infection was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…An increasing number of lncRNAs have been verified to be pivotal regulators in the occurrence and development of an array of human diseases through ceRNA mechanisms, such as cancer, Alzheimer's disease, and cardiovascular disease (Wu et al, 2020;Ma et al, 2020). Additionally, lncRNAs were suggested to mediate insectpathogen interactions via ceRNA regulatory networks (Chen et al, 2019a;Mao et al, 2022). For example, Mao et al (2022) reported that aae-lnc-0165 suppressed by Wolbachia induced the expression of Frontiers in Physiology frontiersin.org REL1 gene in Aedes aegypti through the sequence-specific binding of aae-miR-980-5p, which contributed to the activation of Toll signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of lncRNAs have been verified to be pivotal regulators in the occurrence and development of an array of human diseases through ceRNA mechanisms, such as cancer, Alzheimer's disease, and cardiovascular disease (Wu et al, 2020;Ma et al, 2020). Additionally, lncRNAs were suggested to mediate insectpathogen interactions via ceRNA regulatory networks (Chen et al, 2019a;Mao et al, 2022). For example, Mao et al (2022) reported that aae-lnc-0165 suppressed by Wolbachia induced the expression of Frontiers in Physiology frontiersin.org REL1 gene in Aedes aegypti through the sequence-specific binding of aae-miR-980-5p, which contributed to the activation of Toll signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lncRNAs were suggested to mediate insectpathogen interactions via ceRNA regulatory networks (Chen et al, 2019a;Mao et al, 2022). For example, Mao et al (2022) reported that aae-lnc-0165 suppressed by Wolbachia induced the expression of Frontiers in Physiology frontiersin.org REL1 gene in Aedes aegypti through the sequence-specific binding of aae-miR-980-5p, which contributed to the activation of Toll signaling pathway. Previous findings showed that lncRNA-mediated ceRNA regulatory networks were putatively engaged in midgut development and the N. ceranae response of western honey bee workers (Guo et al, 2018;Chen et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…The strategy to trans-activate RNAi also works when dsRNA is expressed in a transgenic plant and ingested by the Colorado beetle upon feeding [ 106 ], and altogether shows that insects can be affected by ingestion and uptake of dsRNA from external sources. In another very recent study, a long-noncoding RNA lncRNA molecule from the endosymbiont Wolbachia was found to activate anti-dengue defense pathway in Aedes aegypti mosquitoes, indicating the possibilities of ncRNA communication and modulation of virus insect vectors [ 107 ]. Findings such as these, and the important role of endosymbionts in the life cycle of insect pests and/or virus transmission, have also tempted researchers to elaborate on symbiont-mediated RNAi in aphids [ 108 ].…”
Section: Viruses As Modulators Of Srna-based Communication Between Ve...mentioning
confidence: 99%
“…Further, competitive endogenous RNA (ceRNA) network analysis showed these lncRNA enriched for cellular oxidant detoxification pathway. Of them, lncRNA aae-lnc-7598 had the highest upregulation (Mao et al, 2022). Silencing of aae-lnc-7598 resulted in significant downregulation of antioxidant catalase 1B (CAT1B) gene and increase in mitochondria-mediated reactive oxygen species (ROS) in host cells.…”
Section: Wolbachiamentioning
confidence: 99%
“…Silencing of aae-lnc-7598 resulted in significant downregulation of antioxidant catalase 1B (CAT1B) gene and increase in mitochondria-mediated reactive oxygen species (ROS) in host cells. Another lncRNA, aae-lnc-0165 was downregulated after Wolbachia infection in host cells, which increased expression of REL1 through binding of aae-miRNA-980-5p, leading to Toll activation (Mao et al, 2022). Notably, these lncRNAs activate the anti-Dengue Toll pathway during Wolbachia infection.…”
Section: Wolbachiamentioning
confidence: 99%